Abstracts of Philippine researches in social work, 1951-1976 - Ferrer, Susana Santos, 1938-
Author, title and subject indexes are provided to enhance the usefulness of the bibliography and thus facilitate the location of each entry. Numerals in these indexes refer to item numbers not to page numbers.